Effects of the Intervention Programme for a Mexican Adolescent with Absence Epilepsy and Learning Difficulties, Based on the Syndromic Analysis Methodology - Hansel Soto Hernández; Yulia Solovieva; Ernesto V. Ramírez Arroyo; Izabel Hazin (Вестник Московского университета. Серия 14: Психология)
Background. The syndromic analysis methodology allows to discover the mechanisms underlying a particular neuropsychological syndrome and helps to determine the means and methods to overcome difficulties. Objectives. The objective of the present study was to carry out the neuropsychological diagnosis process for an adolescent with difficulties in school learning and epilepsy, with an assessment before and after the application of a neuropsychological intervention programme. Study Participants. The case study refers to a Mexican 13-year-old male student, left-handed. Methods. The type of study was a single case study based on the theoretical-methodological assumptions of historical-cultural neuropsychology. Results. The syndromic analysis methodology allowed us to identify symptomatology related in two aspects: a) difficulties in the planning, regulation and control mechanism of conscious activity, and b) primary motor difficulties with muscle tone impairment. The impact of the applied intervention programme was positive which is expressed not only in the improvement of the difficulties reported in the initial diagnosis (pre-intervention), but also in improvements in the performance of graphic-perceptual and school tasks such as reading, writing and mathematical operations. Conclusions. The effectiveness of neuropsychological treatment is based on the development of a specific intervention programme, tailored to the case study, which contemplates the altered mechanisms, lying at the basis of the cognitive symptoms of a child or an adolescent.